Sea Surface Temperature Relationship of Anchovy Catches in Dodinga Bay Waters - A. Daeng, Ruslan; Tangke, Umar (Agrikan Jurnal Agribisnis Perikanan, 2023)
Increasing the exploitation of anchovy resources is generally done by predicting the fishing area, because anchovy is a small pelagic species and is a neritic resource which is strongly influenced by oceanographic factors in its distribution. Therefore this study was conducted with the aim of analyzing the distribution of sea surface temperature in relation to the catch of anchovies in the waters of Dodinga Bay. This research uses the experimental fishing method by analyzing data in the form of catch data, catch position plot data and sea surface temperature data which is analyzed with geographic information system analysis and statistical analysis which is expected to answer the research objectives. The results showed that the condition of the sea surface temperature distribution during the study was quite fluctuating, ranging from 37.4 oC - 30.0 oC, with anchovy CPUE values in the range of 76.5 - 564.0 kg/trip and these two variables have a close relationship with the regression equation formed. y = -0.876x + 6.9243 with a correlation coefficient (r) of 0.845 and the highest catches are in the temperature range of 27.6 - 29.8 oC. The results of this study are preliminary information so that in an effort to manage anchovy to an optimum level it is necessary to carry out field validation.